2017
DOI: 10.1038/srep41258
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 deficient mesenchymal stem cells fail to establish long-lasting contact with T cells and no longer ameliorate lupus symptoms

Abstract: Systemic lupus erythematosus (SLE) is a multi-organ autoimmune disease characterized by autoantibody production. Mesenchymal stem cells (MSCs) ameliorate SLE symptoms by targeting T cells, whereas the mechanisms of their efficacy remain incompletely understood. In this study, we show that transfer of human MSCs increased MRL.Faslpr mouse survival, decreased T cell infiltration in the kidneys, and reduced T cell cytokine expression. In vitro, allogeneic mouse MSCs inhibited MRL.Faslpr T cell proliferation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Several preclinical studies have demonstrated that hMSCs ameliorate SLE progression in MRL.Fas lpr mice. Lee et al [14] showed that the transfer of hMSCs increased MRL.Fas lpr mouse survival, decreased T cell infiltration in the kidneys, and reduced T cell cytokine expression. Lee et al [24] also showed that hMSCs in combination with prednisone or mycophenolate mofetil had a better therapeutic effect than single therapy in MRL.Fas lpr mice; the following readouts were used in this study: prolongation of survival, decrease in anti-dsDNA and total IgG levels in serum, decrease in cytokine gene expression in spleen cells, and decrease in inflammatory cell infiltration into the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several preclinical studies have demonstrated that hMSCs ameliorate SLE progression in MRL.Fas lpr mice. Lee et al [14] showed that the transfer of hMSCs increased MRL.Fas lpr mouse survival, decreased T cell infiltration in the kidneys, and reduced T cell cytokine expression. Lee et al [24] also showed that hMSCs in combination with prednisone or mycophenolate mofetil had a better therapeutic effect than single therapy in MRL.Fas lpr mice; the following readouts were used in this study: prolongation of survival, decrease in anti-dsDNA and total IgG levels in serum, decrease in cytokine gene expression in spleen cells, and decrease in inflammatory cell infiltration into the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were housed in specific pathogen-free conditions at 21-24°C and 40-60% relative humidity under a 12 h light/dark cycle. Female MRL.Fas lpr mice were injected intravenously with PBS (vehicle, n = 6) or 4 × 10 5 hMSCs/mouse (n = 6) once at the age of 12 weeks [14]. Survival rate and body weight were examined every week.…”
Section: Lupus-prone Mrlfas Lprmentioning
confidence: 99%
See 3 more Smart Citations